Pengaruh Kontrol Diri Terhadap Kedisiplinan Belajar Siswa Di SMPS Bilingual Al Azhar Paciran Lamongan - Syahrizal Hilmi Vega Davella; hasanah, muhimmatul; Ahmad Maujuhan Syah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
This study aims to determine the effect of self-control on student learning discipline at SMPS Bilingual Al Azhar Paciran Lamongan. The sampling technique used in this study was saturated sampling technique, the sample in the study amounted to 61 students at SMPS Bilingual Al Azhar. The measuring instrument in this study is the Indonesian version of the Self-Control Scale with a total of 13 items and a 40-item Learning Discipline scale. The scale used uses a Likert scale with a choice of four alternative answers. The data analysis technique used in this study used simple linear regression. From the results of the research, it can be seen that there is an influence of self-control on student learning discipline at SMPS Bilingual Al Azhar Paciran Lamongan. It is known that the calculated F value is 19.432 with a significance level of 0.000 <0.001. So it can be said that the hypothesis is accepted, meaning that there is an influence of self-control on learning discipline at SMPS Bilingual Al Azhar Paciran Lamongan. The magnitude of the influence of self-control variables on learning discipline is 19.6%.